To solve for 'a', we can start by simplifying both sides of the equation:
a - 8 = 6 + (5a/3)
First, multiply through the equation by 3 to get rid of the fraction:
3(a - 8) = 3(6 + (5a/3))
3a - 24 = 18 + 5a
Next, subtract 3a from both sides of the equation:
3a - 24 - 3a = 18 + 5a - 3a
-24 = 18 + 2a
Now, isolate the 'a' term by subtracting 18 from both sides:
-24 - 18 = 18 + 2a - 18
-42 = 2a
Finally, divide both sides of the equation by 2 to solve for 'a':
-42/2 = 2a/2
-21 = a
Therefore, the solution to the equation is a = -21.
a-8=6+5a/3
1 answer